A Study of Robert Frost’s Mending Wall Through the Lens of Stylistics - Zaib, Farah; Anwar, Reeba (Pakistan Languages and Humanities Review, 2025)
This paper aims to examine the stylistic features of the poem Mending Wall at the lexical, grammatical, phonological, and graphological levels and the contribution of the overall tone and mood of the text in emergence of key themes in the poem. The stylistics field centers on the investigation of linguistic features inherent in literary works. The study adopted Leech and Short's model of stylistic analysis as its framework to explore the interplay between language and meaning. As the research methodology, the study employed close reading for analysis of the stylistic elements. The findings are significant and synthesised all linguistic levels in a single study. The findings also demonstrate how Frost employs stylistic tools to question the necessity of walls in interpersonal relationships, simultaneously critiquing societal norms while promoting introspection. Further studies are recommended to grasp a deeper understanding of the stylistic analysis of literature and its evolving role in literary studies.